Green Alms as Social-Ecological Charities: The Construction of Conservation Fiqh in the Era of Environmental Crisis - Sukrin Nurkamiden; Waliko; Laeli Awaliyah (Journal Of Legal Studies Judex Praetor, 2025)
The recent flash floods and landslides in Sumatra, causing more than 303 fatalities with hundreds still missing, signify that environmental degradation has reached a critical stage. This disaster demonstrates that ecological collapse is no longer theoretical, but has resulted in real loss of life, social disruption, and damaged ecosystems. This article examines green charity as a socio-ecological form of worship within the framework of Islamic ecological jurisprudence. Using a qualitative library-based method, this study analyzes primary sources (Qur’an, Hadith, classical and contemporary fiqh) and secondary references such as scholarly journals and national disaster reports. The findings reveal that environmental conservation can be regarded as ma‘nawiyyah worship and a form of ṣadaqah jāriyah, as protecting the earth aligns with the preservation of life (ḥifẓ al-nafs), wealth (ḥifẓ almāl), and ecological stability (ḥifẓ al-bī’ah). Thus, green charity functions not only as an environmental practice but as an ecological act of devotion rooted in maqāṣid alsharī‘ah. This study concludes that Islamic ecological jurisprudence encourages Muslims to view environmental stewardship as a spiritual obligation, moral responsibility, and collective response to contemporary ecological crises